IMPLIKASI KEBIJAKAN UNTUK MENGATASI KESENJANGAN UPAH GENDER DI LINGKUNGAN KERJA MANUFAKTUR - Syahreza, Dina Sarah; Harmen, Hilma; Zulfri, Andika; Chintia, Ayu; Fonataba, Putri Waiwini; Rahma, Zulaika; Malau, Stephen (Growth, 2024)
Confirming the gender pay gap among Indonesian manufacturing workers is the aim of this research. By using a data collection approach based on reviews, reading sources, and analysis of various references, including books, national journals, international journals, and related articles, the research method used is descriptive qualitative. Despite laws prohibiting gender discrimination in the workplace, research findings show that women are still often paid less than men. The implication of this research is that greater efforts are needed to reduce the gender wage gap in the manufacturing sector. Companies need to improve provisions governing protection, wages and welfare as part of their management, as well as ensure that promotion processes and project assignments are based on individual qualifications, performance and potential, not gender preferences or bias, to achieve better gender equality in manufacturing work environment.